Artificial Intelligence (AI) in the art and design industry / Fahmi Samsudin - Samsudin, Fahmi (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
Artificial intelligence (AI) refers to the capability of machines to perform tasks that traditionally require human intelligence, such as problem-solving, decision-making, and perception. AI is rapidly transforming various industries, including healthcare, finance, transportation, and retail. It encompasses different types, such as rule-based AI using if-then statements for decision-making, machine learning which employs algorithms to analyze and learn from data, and deep learning utilizing artificial neural networks to learn from extensive datasets. AI holds the potential to enhance productivity, accuracy, and effectiveness across sectors. For instance, in healthcare, AI algorithms can analyze medical images for early disease detection. In finance, AI can analyze financial data to identify trends and inform investment decisions. It can optimize traffic flow and safety in transportation and personalize marketing messages in retail. However, the rise of AI also presents challenges, including job displacement and ethical concerns. The increasing capabilities of machines in performing human tasks could lead to widespread job loss. This may result in high unemployment rates and social unrest. Additionally, ethical concerns arise due to AI's potential impact on privacy, bias, and accountability. AI algorithms analyzing large datasets might perpetuate existing biases, leading to discriminatory outcomes. Addressing these challenges requires the development of policies and regulations to ensure responsible AI development and application. This involves investing in education, training programs to prepare the workforce, establishing ethical frameworks for AI use, and fostering collaboration between industry, academia, and government.